PERAN TEKNIK SELF CONTROL UNTUK MENGURANGI PERILAKU SEKSUAL (STUDI KASUS DENGAN KLIEN “A” DI OGAN ILIR) - Hani Haliza; Suryati Suryati; Manah Rasmanah (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
This study entitled "the role of self-control techniques to reduce sexual behavior (a case study with client "A" in Ogan Ilir)". This study aims to describe the sexual behavior of client "A", the factors that influence the sexual behavior of client "A" and determine the role of self-control techniques to reduce the sexual behavior of client "A" in Ogan Ilir. The research uses a qualitative approach with a case study research method. The subjects in this study were client "A" as the primary subject and close friends (boyfriends) as secondary subjects. Data collection techniques used are observation, interviews and documentation. While the data analysis technique used is data reduction, data presentation and drawing conclusions. The results of this study indicate that client "A" engages in sexual activity ranging from holding hands, kissing, hugging, fantasizing/imagining to petting. The factor that causes client "A" to do this is often accessing adult content on social media and social circles. The process of individual counseling with self-control techniques (done 6 meetings) has played a role in reducing the sexual behavior of client "A" both in terms of frequency and intensity.